Pengaruh Akuntabilitas, Kejelasan Sasaran dan Desentralisasi terhadap Kinerja Manajerial di Kota Mojokerto - Makruf, Mukhamat Rifan (Penerbit Goodwood, 2024)
Purpose: This study provides empirical evidence on the influence of performance accountability, clarity of budget targets, and performance decentralization on managerial performance in government agencies in Mojokerto City simultaneously and partially. Methodology/approach: Quantitative research and data collection using questionnaires (saturated sampling). The population was taken from organizations in government agencies in Mojokerto City with a total of 30 agencies and respondents as data samples consisting of heads of departments/agencies, secretaries/equivalents, and heads of fields/sections using SPSS 22. Results/findings: The variables of performance accountability and budget targets have a positive influence on managerial performance, while the variable decentralization of performance has a negative influence. The simultaneous variables of accountability, budget targets, and decentralization have a positive influence on managerial performance. Limitations: The information provided by respondents through the questionnaire does not show their actual opinions due to differences in thoughts, assumptions, and understanding of each respondent. Contribution: This research contributes to the Mojokerto City Regional Government.